Angiogenesis Inhibitors for the Treatment of Hepatocellular Carcinoma - Berretta, Massimiliano; Rinaldi, Luca; Di Benedetto, Fabrizio; Lleshi, Arben; De Re, Vallì; Facchini, Gaetano; De Paoli, Paolo; Di Francia, Raffaele (Frontiers in Pharmacology, 2016)
Background: Angiogenesis inhibitors have become an important therapeutic approach in the treatment of hepatocellular carcinoma (HCC) patients. The therapeutic inhibition of angiogenesis of Sorafenib in increasing overall survival of patients with HCC is a fundamental element of the treatment of this disease. Considering the heterogeneous aspects of HCC and to boost therapeutic efficacy, prevail over drug resistance and lessen toxicity, adding antiangiogenic drugs to antiblastic chemotherapy (AC), radiation therapy or other targeted drugs have been evaluated. The matter is additionally complicated by the combination of antiangiogenesis with further AC or biologic drugs. To date, no planned approach to understand which patients are more responsive to a given type of antiangiogenic treatment is available. Conclusion: Large investments in the clinical research are essential to improve treatment response and minimize toxicities for patients with HCC. Future investigations will need to focus on utilizing patterns of genetic information to classify HCC into groups that display similar prognosis and treatment sensitivity, and combining targeted therapies with AC producing enhanced anti-tumor effect. In this review the current panel of available antiangiogenic therapies for the treatment of HCC have been analyzed. In addition current clinical trials are also reported herein.